Sinus bradycardia and acute renal injury secondary to Viperidae snakebite: first case report - Guamán-Charco, Elías David; Paredes-Ponce, Anabel; Orellana-Chimbay, Hugo; Omares, Nelson; Guamán-Charco, Genesis; Rubio, Mario; Vasconez-Gonzalez, Jorge; Ortiz-Prado, Esteban (Frontiers in Medicine, 2025)
BackgroundWorldwide, millions of people suffer from snakebites every year. In Ecuador, as of epidemiological week 30 of 2024, approximately 271 cases have been reported.Clinical caseA 54-year-old male patient suffered a snakebite from the Viperidae family 24 h ago, on his right upper limb. Classified as moderate envenomation, he was given antivenom and admitted to the hospital. During his stay, he began to show clinical and paraclinical alterations, including sinus bradycardia on the electrocardiogram and acute renal injury, requiring dialysis therapy sessions. In daily ECG controls on day 13, the heart rate normalized. However, after day 22, he was discharged but remained under triweekly dialysis therapy.ConclusionComplications from snakebites are rare, both cardiovascular and renal, but can be potentially fatal without early detection and timely treatment.